Small-Molecule Transport by CarO, an Abundant Eight-Stranded β-Barrel Outer Membrane Protein from Acinetobacter baumannii. Issue 14 (17th July 2015) - Zahn, Michael; D'Agostino, Tommaso; Eren, Elif; Baslé, Arnaud; Ceccarelli, Matteo; van den Berg, Bert
Abstract: Outer membrane (OM) β-barrel proteins composed of 12–18 β-strands mediate cellular entry of small molecules in Gram-negative bacteria. Small OM proteins with barrels of 10 strands or less are not known to transport small molecules. CarO ( car bapenem-associated o uter membrane protein) from Acinetobacter baumannii is a small OM protein that has been implicated in the uptake of ornithine and carbapenem antibiotics. Here we report crystal structures of three isoforms of CarO. The structures are very similar and show a monomeric eight-stranded barrel lacking an open channel. CarO has a substantial extracellular domain resembling a glove that contains all the divergent residues between the different isoforms. Liposome swelling experiments demonstrate that full-length CarO and a "loop-less" truncation mutant mediate small-molecule uptake at low levels but that they are unlikely to mediate passage of carbapenem antibiotics. These results are confirmed by biased molecular dynamics simulations that allowed us to quantitatively model the transport of selected small molecules. Graphical abstract: Highlights: CarO ( car bapenem resistance o uter membrane protein) from A . baumannii forms an eight-stranded β-barrel with a large extracellular domain. Crystal structures show that the channel through the CarO barrel is closed at two locations. Liposome swelling experiments and molecular dynamics simulations demonstrate CarO-mediated substrate uptake for glycine and ornithine but not for glutamate and imipenem. Small-molecule uptake extends the repertoire of possible functions mediated by eight-stranded β-barrels.